Recovery of vanadium element from wastewater of petroleum refineries using effective adsorbent: Mathematical approach via isothermal, kinetics and thermodynamic simulation - Shadhan, Zainab Jabbar Shadhan; Alhamd, Salem; Abbas, Mohammed Nsaif (Al-Qadisiyah journal for engineering science, 2024)
Adsorption behavior can be determined using different essential studies such as adsorption isotherm, kinetics, and thermodynamics. In this study, adsorption isotherm models, and kinetic, and thermodynamics studies are used to describe the use of alumina as an effective adsorbent and a remover of vanadium (V+5) ions from aqueous solutions contaminated by this metal. The aqueous solutions used simulate the wastewater of most traditional oil refineries. Efficiency can be determined by comparing the correlation coefficients of the linear relationships used with each model. Using alumina, the perfect removal of vanadium ions was achieved. Vanadium removal increases with an increase in the operating conditions, which are time temperature, agitation speed, pH, and adsorbent’s media dose. However, it also increases with the elimination of the initial concentration. This study shows that the vanadium’s adsorption based on the Langmuir isotherm model gives a correlation coefficient of 0.9999, while when it is based on the Temkin and Freundlich isotherms the correlation coefficient is less. Hence, adsorption on the surface of alumina takes place in monolayer surfaces with a regular distribution of particle’s binding energy and a narrow quantity of identical sites on the surface of alumina. Subsequently, the kinetic study shows that the adsorption behavior matched the pseudo-second-order kinetic model with R2 equaling 0.9999. Also, thermodynamics studies approves that the adsorption is a spontaneous endothermic process of enthalpy change.